The Alternative Care of Children for Career Families for Fulfilling Children's Rights (Studies in Aisyiyah, Trenggalek Day care) - Zahro, Fathin Aqidatus (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Children are a gift from God Almighty and have inherent rights that must be recognized and fulfilled by parents, in particular, and by the community and also the state. However, as time progressed, the number of women working in the public sector increased, which in this case resulted in the child-rearing process at home not being optimal. In the end, they switched the child care from their parents to alternative caregivers. The purpose of this study is to find out the supporting and inhibiting factors for the implementation of parenting and how the strategy for Aisyiyah's Care Center is to fulfill children's rights. This research uses a qualitative approach and is a type of empirical research. This study obtained data from the field by means of interviews and documentation. The research subjects used were the Head of Caregivers, caregivers, and parents of foster children. The results of this study indicate that; (1) supporting factors for the implementation of care, namely: adequate support facilities for children, good communication between caregivers and parents of children; inhibiting factors for care, namely: the number of caregivers and children is not comparable, limited funds, and there is no separation of responsibilities for caregivers in providing care and education. (2) the strategy for implementing care in Aisyiyah Child Care Center, namely by instilling in children the principles of foster care, compassion, nurture, and forging in order for rights to be fulfilled properly and maximally